A Comprehensive Analysis of School-Based Support for Children with ADHD and Oppositional Defiant Disorder: Insights from Parental Perceptions - VB, Devapramod (Yayasan Sinergi Kawula Muda, 2024)
Children with behavioral disorders, such as ADHD and oppositional defiant disorder, face significant academic and social challenges in primary schools. This study examines parents' perceptions of educational support for these children, highlighting the adequacy of existing programs and the challenges faced in accessing essential services. Using a qualitative case study approach, in-depth interviews were conducted with parents, teachers, and students in Jakarta. The findings reveal that while some schools attempt to provide support, gaps remain in specialized interventions, teacher training, and communication between parents and educational institutions. Parents reported difficulties in obtaining necessary resources and felt inadequately included in decision-making processes regarding their children's education. Teachers also struggled due to limited institutional guidance on managing behavioral disorders. The study underscores the importance of tailored interventions, improved teacher training, and enhanced parental involvement in educational policymaking. The findings contribute to the broader discourse on inclusive education and emphasize the necessity for structured, evidence-based strategies to support children with behavioral disorders. Policymakers and educators must work collaboratively to implement policies that enhance accessibility and inclusivity in primary education. Future research should assess the long-term impact of intervention programs and explore ways to strengthen the partnership between schools and families.